2016
DOI: 10.1371/journal.pone.0159816
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobinopathy Awareness among Young Students in Turkey: Outcomes of a City-Wide Survey

Abstract: The success of prevention programs demonstrated the importance of raising awareness about haemoglobinopathies since the lack of knowledge and awareness about the disorders may serve as barriers to prevention, disclosure of disease status as well as to testing for haemoglobinopathies. The aim of this study is to investigate the knowledge and attitudes of middle and high school students towards haemoglobinopathies in Hatay, where the disorders are prevalent. This cross-sectional study was conducted on 8th and 9t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…We found that the level of thalassaemia awareness was surprisingly low, and only one-third of the respondents (33%, n = 1578) had heard of thalassaemia. Being situated in the world's thalassaemia belt with an estimated carrier of about 6-12%, this result is quite unexpected [4] as compared to other thalassaemia-prevalent countries such as Malaysia (~87%), Italy (85%), Greece (95%), Bahrain (65%), Turkey (58%) and Saudi Arabia (48%) [12,[22][23][24][25][26]. This indicates that a major public health concern has been overlooked in Bangladesh.…”
Section: Poor Knowledge and Attitudementioning
confidence: 99%
See 1 more Smart Citation
“…We found that the level of thalassaemia awareness was surprisingly low, and only one-third of the respondents (33%, n = 1578) had heard of thalassaemia. Being situated in the world's thalassaemia belt with an estimated carrier of about 6-12%, this result is quite unexpected [4] as compared to other thalassaemia-prevalent countries such as Malaysia (~87%), Italy (85%), Greece (95%), Bahrain (65%), Turkey (58%) and Saudi Arabia (48%) [12,[22][23][24][25][26]. This indicates that a major public health concern has been overlooked in Bangladesh.…”
Section: Poor Knowledge and Attitudementioning
confidence: 99%
“…Data on knowledge and attitude about thalassaemia were collected using a structured questionnaire. The design of the study questionnaire was based on a review of studies found in the literature [12,[25][26][27]40], and after consultation with experts including clinicians, public health researchers and a statistician. The questionnaire, which consisted of 22 questions divided into 2 parts, was prepared in the Bengali language, however, some of the medical terminologies could not be directly translated.…”
Section: Instrumentmentioning
confidence: 99%
“…On the other hand, neighbouring countries such as Malaysia had already implemented thalassaemia screening programme at school since 2016. 32 Association between KAP and sociodemographic factors Good KAP was more prevalent among young adults (age [19][20][21][22][23][24] than adolescents (age 15-18), as older youth with higher education generally had higher literacy to better understand thalassaemia from books and social media. 33 Women were more likely to have good KAP, which was consistent with findings from studies in Iran 33 34 and Bahrain.…”
Section: Attitudementioning
confidence: 99%
“…Premarital screening programmes have been shown to be successful in reducing cases of hemoglobinopathies in countries such as Turkey and Saud Arabia (Okyay, Çelenk, Nazlıcan & Akbaba). Also, Okyay et al (2016) highlighted the importance of creating awareness and knowledge about the disorders to encourage would-be spouses to attend genetic counseling clinics before considering marriage.…”
Section: Importance Of Genetic Testing For Sickle Cell Disease In Nigmentioning
confidence: 99%